Social Media as a Catalyst for Supporter Conflicts and Riots in Indonesia - Tenriliweng, Andi Ahmad Hasan; Fridayanti, Novia (Universitas Muhammadiyah Yogyakarta, 2025)
In the digital age, social media has become a primary means of communication and interaction among football supporters in Indonesia. Beyond serving as a platform for sharing information and building communities, social media also acts as a catalyst for conflict between supporters, sometimes escalating into riots. This study aims to analyze how social media facilitates the spread of provocation, hate speech, and misinformation, which contribute to heightened tensions between supporter groups. Employing a qualitative case study methodology, the research examines several instances of fan conflict in Indonesia that were triggered by social media activity, including the communication patterns used by fans of Indonesia’s League 1 and League 2 clubs. The findings reveal that social media accelerates and broadens the reach of provocative content, reinforces polarization, and intensifies rivalries through emotionally charged and partisan narratives. Moreover, social media algorithms tend to amplify exposure to such content, thereby increasing the likelihood of real-world conflicts. In conclusion, while social media holds the potential to foster solidarity among football supporters, without proper regulation and digital literacy, these platforms can become key drivers of unrest with harmful consequences for multiple stakeholders.